Volume 4: Turbo Expo 2007, Parts a and B 2007
DOI: 10.1115/gt2007-27419
|View full text |Cite
|
Sign up to set email alerts
|

Film Cooling From a Row of Holes Supplemented With Anti Vortex Holes

Abstract: The primary focus of this paper is to study the film cooling performance for a row of cylindrical holes each supplemented with two symmetrical anti vortex holes which branch out from the main holes. The anti-vortex design was originally developed at NASA-Glenn Research Center by Dr. James Heidmann, co-author of this paper. This “anti-vortex” design is unique in that it requires only easily machinable round holes, unlike shaped film cooling holes and other advanced concepts. The hole design is intended to count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 17 publications
6
42
0
Order By: Relevance
“…The hole diameter and Reynolds number and the plenum condition from this past study are consistent with the current work. It can be seen that there is a large amount of area downstream of a hole that is not covered at all by the coolant, which is typical of straight cooling holes and has been studied extensively in previous work [7] [10]- [16]. The hole spacing is three hole diameters as is consistent with practice in real engines for cylindrical holes.…”
Section: Contour Plots Of Effectivenesssupporting
confidence: 58%
See 3 more Smart Citations
“…The hole diameter and Reynolds number and the plenum condition from this past study are consistent with the current work. It can be seen that there is a large amount of area downstream of a hole that is not covered at all by the coolant, which is typical of straight cooling holes and has been studied extensively in previous work [7] [10]- [16]. The hole spacing is three hole diameters as is consistent with practice in real engines for cylindrical holes.…”
Section: Contour Plots Of Effectivenesssupporting
confidence: 58%
“…Dhungel et al [7] reported that for a single hole geometry case, similar to that shown in Figure 6, the cooling hole effectiveness reduces as the blowing ratio is increased from 1.0 to 2.0. A study conducted by Kim and Hassan [1] with a single hole geometry by using RANS and URANS simulations with blowing ratio 1.0 showed that the predicted maximum cooling effectiveness along the centerline was less than 0.5 and this occurs only at a limited x/d region.…”
Section: Contour Plots Of Effectivenessmentioning
confidence: 50%
See 2 more Smart Citations
“…Consequently, it improves the film effectiveness compared to a standard hole case for the same blowing ratios. Dhungel et al [7] further confirm the superiority of the anti-vortex cooling hole by investigating it performance four different blowing ratios. The results indicate better downstream and lateral film coverage leads to improved overall film cooling effectiveness.…”
Section: Literature Reviewmentioning
confidence: 78%